Customer Satisfaction Analysis : The Role of Communication, Social Behaviour and Customer Experience with Trust as a Mediating Variable at Pematang Siantar Class II Check Point Immigration Office - Septian Yubil Sumurung Sihombing; Elfitra Desy Surya; Husni Muharram Ritonga (Equivalent : Journal of Economic, Accounting and Management, 2026)
This research aims to analyze the effects of communication, social behaviour, and customer experience on customer satisfaction with trust as a mediating variable at Pematang Siantar Class II Check Point Immigration Office. The research employs a quantitative explanatory approach using primary data collect from 372 passport applicants. Data were analyzed using the Partial Least Squares-Structural Equation Modelling (PLS-SEM) technique with SmartPLS. The results indicate that customer experience has a positive and significant effect on customer satisfaction both directly and indirectly through trust. Trust is proven to have a positive and significant effect on customer satisfaction and plays a crucial mediating role in the relationship between communication, social behaviour, and satisfaction. Although communication and social behaviour do not have a significant direct effect on customer satisfaction, both variables significantly influence trust, which subsequently enhances satisfaction. The model demonstrates a moderate explanatory power, indicating that service related variables and trust substantially contribute to public satisfaction in immigration services. These findings suggest that customer satisfaction in public service institution is more strongly influenced by experiental and relational factor than by procedural interactions alone. Therefore, improving customer experience and strengthening publis trust should be strategic priorities in immigration service delivery. Therefore, improving customer experience and strengthening publis trust should be strategic priorities in immigration service delivery. This research contributes to public service management literature by reinforcing trust as a key psychological mechanism linking service quality attributes to customer satisfaction.